A monarquia absolutista em xeque: a soberania no pensamento de Rousseau e as críticas aos poderes ilegítimos - ROSA, Ruan Cláudio da Silva (2018)
In this research, we intend to point out the singularity of the sovereignty´s conception developed by Jean-Jacques Rousseau (1712-1778) in his work from Social Contract, published in 1762, and thus understand the way in which the author would go insert himself into the intellectual debate of the time concerning the sovereignty´s issue. We will use as sources other works from Rousseau, especially the discourse about the origin and foundation of Inequality among men, since, we understand that for a better comprehension about Social Contract emerges as need to rethink relations between these two works. The research ´s clipping concentrates more directly on the analysis about book I and II from the work Social Contract, since, this is the passage of this work that directly addresses the issues related to the foundations of the social pact and sovereignty. Interpreting the rousseaunian text, we will use as theoretical input some conceptions connected to the historical and dialectical materialism and also we will consult the theoretical -methodological framework named linguistic or radical contextualism, method disseminated by the English historian Quentin Skinner, which has as a central point the need to insert the studied text to the socio-historical and intellectual context in which it was developed. For this purpose, we seek to analyze its historical context, author formation, and the main concepts regarding to his political theory. Through intertextuality, we intend to reflect about how his text insert itself in relation to the political thinkers of his time, and thus reflect if the work serves as an answer or refutation to some questions of that period. At this point, we move into the question of possible readings of Social Contract work, taking a risk about thinking a very criticized aspect of the developed model by Quentin Skinner which consists of the need to think the author´s purpose behind the writing of the analyzed work.